2018
DOI: 10.3390/nu10101436
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Protein Restriction Alters the Renal Ptger1 DNA Methylation State in SHRSP Offspring

Abstract: We previously reported that maternal protein restriction (LP) during pregnancy increases salt sensitivity in offspring using the Stroke-Prone Spontaneously Hypertensive Rat (SHRSP). In the present study, we focus on DNA methylation profiles of prostaglandin E receptor 1 gene (ptger1), which is known to be associated with hypertension. We evaluated the ptger1 DNA methylation status via bisulfite sequencing, and analyzed the expression of ptger1-related genes. The results of these analyses showed that, compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…Our in vivo experiments using SHRSP rats confirmed the in vitro results and corroborated previous studies (Miyoshi et al., 2018; Otani et al., 2004, 2012). Specifically, SHRSP offspring exposed to a low‐protein fetal environment and salt loading in adulthood showed significantly elevated blood pressure as well as altered renal AT2R protein levels.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our in vivo experiments using SHRSP rats confirmed the in vitro results and corroborated previous studies (Miyoshi et al., 2018; Otani et al., 2004, 2012). Specifically, SHRSP offspring exposed to a low‐protein fetal environment and salt loading in adulthood showed significantly elevated blood pressure as well as altered renal AT2R protein levels.…”
Section: Discussionsupporting
confidence: 92%
“…This link occurs because environmental stress alters the epigenome, particularly DNA methylation profiles (Bogdarina et al., 2007; Heijmans et al., 2008). We previously reported that exposing SHRSP fetuses to protein restriction accompanied by altered methylation and elevated gene expression of prostaglandin E Receptor 1 ( Ptger1 ), one of the key mediators of sodium retention (Miyoshi et al., 2018) Additionally, perinatal nicotine exposure altered site‐specific AT2R promoter CpG methylation and repressed its gene expression in the brain, increasing brain hypoxic‐ischemic injury in neonatal rats (Li et al., 2012, 2013). Thus, we hypothesized that the characteristic AT2R protein expression observed in our previous study was due to altered AT2R methylation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 68 73 ] Furthermore, experimental animal models also provide strong supporting evidence. Modulation of maternal diet, including a HFD, [ 74 , 75 ] low-protein diet, [ 76 , 77 ] and calorie restriction [ 78 80 ] during pregnancy and lactation resulted in a persistent shift in DNA methylation levels of metabolism specific genes in offspring, which were associated with their metabolic disorders.…”
Section: Role Of Epigenetics In Mediating the Metabolic Programmingmentioning
confidence: 99%
“…Besides the above programming insults, maternal protein restriction has been established as a common developmental origin of hypertension. Studies in rodents have consistently reported that 6-9% protein restriction in pregnant mothers resulted in hypertension in adult offspring (14)(15)(16)(17). Previous studies led to several hypotheses about the underlying mechanisms, involving the suppression of the newborn renin-angiotensin system (18), impairment to nephrogenesis (19), triggering oxidative disruption in the medulla oblongata (20), or hindering the hypothalamic-pituitary-adrenal axis (21).…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that maternal protein restriction modulates the methylation state of the renal prostaglandin E receptor 1 gene ( Ptger1 ), a key regulator of hypertension, in the stroke-prone spontaneously hypertensive (SHRSP) rat model ( 17 ). In the present study, we administered SHRSP pups diets with different amounts of protein after a state of fetal protein restriction to investigate whether postnatal protein supplementation could rectify the negative changes in DNA methylation under malnutrition in pregnancy.…”
Section: Introductionmentioning
confidence: 99%